Literature Review of the New Role of Atropine Eye Drop on Children's Myopia Progression - Tanjung, Melita Novianne; Nikiyuluw, Renna Sara; Sombuk, Berlin Clara Yustinah; Anugrahsari, Santi (Jurnal MedScientiae, 2024)
Myopia is one of the most common refractive disorders, especially in children. It can increase the risk of degenerative eye diseases. Various studies have been conducted to date to show the potential of variations of atropine in inhibiting the progression of myopia. This scientific article summarizes the various research, mainly related to the effectiveness of atropine on myopia. The research method uses "Literature Review" by searching Pubmed and Google Scholar with the English keywords ((“Myopia” OR “Refractive error”) AND “Children” AND “Atropine” AND “Progression”), 2018 until 2023. The discussion summarizes the role of atropine in myopia and its effectiveness and safety. Future research is expected to explore, more specifically, the role of atropine in inhibiting the progression of Myopia.